Hot Spots in a Network of Functional Sites - ÖZBEK SARICA, PEMRA (PUBLIC LIBRARY SCIENCE, 2013)
It is of significant interest to understand how proteins interact, which holds the key phenomenon in biological functions. Using dynamic fluctuations in high frequency modes, we show that the Gaussian Network Model (GNM) predicts hot spot residues with success rates ranging between S 8-58%, C 84-95%, P 5-19% and A 81-92% on unbound structures and S 8-51%, C 97-99%, P 14-50%, A 94-97% on complex structures for sensitivity, specificity, precision and accuracy, respectively. High specificity and accuracy rates with a single property on unbound protein structures suggest that hot spots are predefined in the dynamics of unbound structures and forming the binding core of interfaces, whereas the prediction of other functional residues with similar dynamic behavior explains the lower precision values. The latter is demonstrated with the case studies; ubiquitin, hen egg-white lysozyme and M2 proton channel. The dynamic fluctuations suggest a pseudo network of residues with high frequency fluctuations, which could be plausible for the mechanism of biological interactions and allosteric regulation.
Keywords: PROTEIN-PROTEIN INTERACTIONS; LIGAND-BINDING; CONSERVED RESIDUES; STRUCTURAL BASIS; PROTON CHANNEL; FREE-ENERGY; IDENTIFICATION; RECOGNITION; PREDICTION; INTERFACES